Validity : theoretical development and integrated arguments - Chalhoub-Deville, Micheline; O'Sullivan, Barry (Sheffield, South Yorkshire ; Bristol, CT : Equinox Publishing Ltd, 2020)
"This monograph provides a historical overview of validity, targeting developments in both the UK and the US. It explores theoretical notions of validity as well as pragmatic validation practices and expands the arguments that need to be attended to document quality"--
Includes bibliographical references and index.
Keywords: Examinations -- Validity